2021
DOI: 10.3390/ijerph18073453
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Psychological Distress in Women with Endometriosis: The Role of Multimorbidity, Body Image, and Self-Criticism

Abstract: While large numbers of women report high levels of psychological distress associated with endometriosis, others report levels of distress that are comparable to those of healthy women. Thus, the aim of the current study was to develop an explanatory model for the effect of endometriosis on women’s psychological distress. Furthermore, it sought to further investigate the role of body image, self-criticism, and pain intensity on the psychological distress associated with endometriosis and establish the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
(28 reference statements)
2
13
0
Order By: Relevance
“…Body dissatisfaction, a proxy for negative body image, has been associated with infertility and dyspareunia in endometriosis [22], consistent with findings of research investigating body image distress in gynecological cancer [23]. Moreover, more negative body image has been associated with increased self-criticism in endometriosis populations, a factor that is incompatible with body functionality appreciation [20]. Another factor likely to exacerbate negative responses to an endometriosis-affected body is the nature of endometriosis being encased within menstrual social taboos that may increase vulnerability to body image distress due to diminished social supports [24].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Body dissatisfaction, a proxy for negative body image, has been associated with infertility and dyspareunia in endometriosis [22], consistent with findings of research investigating body image distress in gynecological cancer [23]. Moreover, more negative body image has been associated with increased self-criticism in endometriosis populations, a factor that is incompatible with body functionality appreciation [20]. Another factor likely to exacerbate negative responses to an endometriosis-affected body is the nature of endometriosis being encased within menstrual social taboos that may increase vulnerability to body image distress due to diminished social supports [24].…”
Section: Introductionsupporting
confidence: 75%
“…Emerging research has identified considerable negative impacts of endometriosis on body image [19,20], particularly for those with extensive disease [21] and younger adults [19]. Qualitative research [22] highlights widespread negative body image impacts linked to hormonal treatment weight gain and scarring from surgery, with concealment practices (e.g., wearing loose clothing) utilized as a means of coping with these bodily changes.…”
Section: Introductionmentioning
confidence: 99%
“…Women with deep endometriosis, a severe sub-type, were found to be correlated with worse body image (Melis et al, 2015). Geller et al (2021) investigated the roles of multi-morbidity, body image, and self-criticism as predictors of psychological distress in women with endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…The Patient Health Questionnaire (PHQ-9) is a unidimensional depression scale for diagnosing depressive and other mental disorders [ 68 ]. The PHQ-9 has been validated in an endometriosis population, proving its good psychometric properties [ 69 ]. Its use in routine care using a digital tool has been proved in neurologic patients [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The General Anxiety Disorder-7 (GAD-7) scale is an instrument with an unidimensional structure that measures the severity of generalized anxiety disorders (pain disorders, social anxiety disorder, and posttraumatic stress disorder) [ 72 ]. The GAD-7 has been validated in an endometriosis population, proving its good psychometric properties [ 69 ].…”
Section: Resultsmentioning
confidence: 99%